(untitled) (Fiep Bulletin - online, 2014)
With the marketing changes that come occurring, the academies and the managers they must identify the threats, and the chances of its company, not allowing a daily growth without no enterprise vision. The strategical planning (PE) assists in this relation, with the use of itens for maintenance and progression of markets in companies of all the branches also of the academies thus aiming at to optimize marketing actions of increase of the capital. With this the general objective of this study was to verify the enterprise knowledge, autilização and the level of importance attributed to the strategical planning, of the operating and not operating academies of the zone west of the Rio de Janeiro. For if dealing with a research changeable dependent eindependente had been controlled can dissertar that this research if classifies as being direct, experimental of the type of field. This study in 12 academies of the quarter of the zone is delimited west of the Rio de Janeiro being 6 academies that act in market and 6 that they do not act in the market. With at least 2 years of performance for both the groups. With intention to cure the problematic one presented for this research, we had the presentation of referring results to the knowledge, use and degree of main agreement of itens that it composes the strategical planning. We can then affirm that itens of the strategical planning with bigger factor of use and operating enterprise knowledge of the sample in relation the not operating sample had been the Swot analysis and the analysis of scene. We suggest the future studies the identification of intervening variable, that estabeleçam relation cause and effect with the removal of companies of the market of work and through an multifactorial analysis of these variable can elucidate this so obscure process better.